Analysis Of Voltage Sensor Based On Optical Fiber Macrobending Structure Using Piezoelectric For 1500 – 1600 Nm Wavelength - Dwi Satriananda; Erna Sri Sugesti; Ali Muayyadi (eProceedings of Engineering, 2017)
The integration of the optical fiber and piezoelectric macrobending structures can be utilized to create a voltage sensor. Both are arranged in such a way that optical fibers form a half or a circle whose position is between two piezoelectric. The piezo characteristic used is a one-way length dimension if applied voltage. So, when the piezo is given a certain voltage, then the optical fiber form, which was originally a half or a circle, will be shaped into an ellipse, because piezo length changes will push the cable from left and right. In addition to the changes in the shape of optical fiber, the distance between piezo, number of turn and cable characteristics used also affect the changes in macrobending loss.Â